Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/s1472-6483(10)60014-4
|View full text |Cite
|
Sign up to set email alerts
|

Zona pellucida birefringence score and meiotic spindle visualization in relation to embryo development and ICSI outcomes

Abstract: The meiotic spindle and the zona pellucida exhibit molecular order when imaged with polarized optics. This study aimed to investigate possible factors contributing to the zona pellucida birefringence score and meiotic spindle visualization, and to evaluate whether these structures may predict intracytoplasmic sperm injection outcomes. Oocytes were divided into groups according to zona pellucida birefringence and meiotic spindle visualization. In addition, the cycles were split into three groups based on the zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 30 publications
2
55
1
2
Order By: Relevance
“…Birefringence of the spindle and the zona of the metaphase II oocyte, as evaluated by polarized light microscopy, have been recently proposed as criteria of quality in live human oocytes [13,23,24]. Several studies have reported a positive correlation between high birefringence of the zona pellucida (HZB) and that of the spindle (SP) in metaphase II oocytes, and the main reproductive indexes such as fertilization, embryo implantation and women's pregnancy rate [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Birefringence of the spindle and the zona of the metaphase II oocyte, as evaluated by polarized light microscopy, have been recently proposed as criteria of quality in live human oocytes [13,23,24]. Several studies have reported a positive correlation between high birefringence of the zona pellucida (HZB) and that of the spindle (SP) in metaphase II oocytes, and the main reproductive indexes such as fertilization, embryo implantation and women's pregnancy rate [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…New methodologies, including polar body diagnosis (PBD) [9], metabolomics [10], polarization light microscopy [11][12][13][14][15] and pattern recognition of processed images by special algorithms [16], have been proposed as methods to improve the objective selection of good quality oocytes. In particular, the PolScope was used in a semiquantitative mode to evaluate the birefringence of the ZP [17] and the meiotic spindle (SP) of metaphase II oocytes [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…У некоторых ооцитов, имеющих первое полярное тельце, может не быть видимого в поляризационном микроскопе веретена деления. Поляризационная микроскопия дает возможность оценки веретена де-ления и позволяет прогнозировать течение процесса оплодотворения и последующего дробления развив-шегося в результате оплодотворения эмбриона [11,12].…”
unclassified